2019
DOI: 10.1136/bmjopen-2018-028259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lumbar extensor muscle strengthening and neuromuscular control retraining on disability in patients with chronic low back pain: a protocol for a randomised controlled trial

Abstract: IntroductionChronic low back pain (CLBP) is the leading cause of disability worldwide. However, there is no consensus in the literature regarding optimal management. Exercise intervention is the most widely used treatment as it likely influences contributing factors such as physical and psychological. Literature evaluating the effects of exercise on CLBP is often generalised, non-specific and employs inconsistent outcome measures. Moreover, the mechanisms behind exercise-related improvements are poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Measurement of the IL muscle thickness was defined by the distance between the inside of the superior fascial border and the inferior fascial border (Figure 1c). LM and IL echogenicity was measured by (i) performing a circumferential trace of the inner fascial border of each muscle 30,31 and (ii) performing greyscale histogram analysis of the muscle area of interest. Echogenicity is a measure of acoustic reflectance 19 with ranges varying from 0 to 255: zero represents an inability to reflect ultrasound waves with the image appearing black whereas 255 represents complete reflection of ultrasound waves with the image appearing white 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of the IL muscle thickness was defined by the distance between the inside of the superior fascial border and the inferior fascial border (Figure 1c). LM and IL echogenicity was measured by (i) performing a circumferential trace of the inner fascial border of each muscle 30,31 and (ii) performing greyscale histogram analysis of the muscle area of interest. Echogenicity is a measure of acoustic reflectance 19 with ranges varying from 0 to 255: zero represents an inability to reflect ultrasound waves with the image appearing black whereas 255 represents complete reflection of ultrasound waves with the image appearing white 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Exercise therapy has been demonstrated to be effective in decreasing pain compared with non-exercise-based treatments in adults [11], with such improvements thought to reflect some combination of the exercise-related physical and psychological adaptations. Exercise therapy is the most widely used non-pharmacological treatment, comparable to other conservative treatments for improving disability and pain intensity in CLBP [8,12,13]. Two recent systematic reviews reported that exercise training is an effective treatment for reducing pain in patients with CLBP; however, they both highlighted that it is still unclear exactly what forms of exercises are most effective or which mechanisms may most likely explain such improvements [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, after the participants had provided written consent for participation, they were educated about the etiology, natural course, and surgical treatment of PDSI; they underwent brief training on the importance of core and lumbar extensor muscle strengthening exercises (lumbar extension, hip extension, trunk flexion, and leg press exercise) and rest. [13][14][15]…”
Section: Radiological and Clinical Evaluationmentioning
confidence: 99%